REAKSI TUTURAN ANAK USIA DINI TERHADAP KALIMAT IMPERATIF POSITIF DAN NEGATIF ORANG TUA - Muhajir Muhajir (EDU-KATA, 2018)
The purpose of research are to describe on responding discourse of the child that given by their parents. With the result of t the research, parent can understand how to use imperative sentence to their child well. This research uses describtive qualitative method, explain the act of childhood for positive and negative imperative sentence by parents. Data of this research is responding action of childhood, the source of data take form research object with four child, consist: 1 to 4 year old. This research use technique observation, filed data, and documentation. Childhood responses positive imperative sentences that explained by their parents then they can response like their parents mean. Where as with negative imperative sentences they can also response well. So, base on this research data, parents must more careful in using imperative sentences to their child. Their child mus be given positive value in building their character.